2012
DOI: 10.1519/jsc.0b013e31825c2bef
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Ankyrin Repeat Domain 6 Gene (ANKRD6) and Muscle and Physical Activity Phenotypes Among European-Derived American Adults

Abstract: Ankyrin repeat domain 6 (ANKRD6) is a ubiquitous protein that associates with early development in mammals and is highly expressed in the brain, spinal cord, and heart of humans. We examined the role of 8 ANKRD6 single-nucleotide polymorphisms (SNPs) on muscle performance and habitual physical activity (PA). Single-nucleotide polymorphisms were 545 T>A (rs9362667), 485 M>L (rs61736690), 233 T>M (rs2273238), 128 I>L (rs3748085), 631 P>L (rs61739327), 122 Q>E (rs16881983), 197805 G>A (rs9344950), and 710 L>X (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published literature on MARPs in muscle hypertrophy is focused on cardiac muscle. However, it is noteworthy that polymorphic variants of Ankrd6 in humans are associated with skeletal muscle size and the magnitude of RT-induced muscle hypertrophy (Van Deveire et al 2012). Cumulatively, the findings suggest that these sarcomere-related proteins may play a role in RT hypertrophy signaling, although more work is needed.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…Thus, it appears NOS3 +894 G>T may habitually influence the preference of light PA, vigorous PA and sitting and the strength gains in women that can result from an RT program. These findings suggest NOS3 +894 G>T may be important to consider for a personalized approach to exercise prescription along with a growing number of genetic variants that have been reported to be associated with muscle performance [15,[24][25][26][27] and habitual PA [21,[28][29][30][31][32]. For example, when recommending exercise to adults for its overall health benefits, the NOS3 +894 G>T and PA intensity dependent genotype differences we found could be considered when counseling people to become more physically active due to what appears to be a genetic predisposition to prefer light over vigorous intensity PA among those with the TT genotype.…”
Section: Discussionmentioning
confidence: 94%
“…The experimental design of FAMuSS has been described elsewhere [6,[15][16][17][18][19][20][21]. The institutional review boards from the 10 institutions involved with the study approved the study protocol and informed consent was obtained from all individuals prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%